Tutor Competence in Online-Learning Service within Distance Education - Jamil; Patmawati Halim; Hasanuddin (Didaktika: Jurnal Kependidikan, 2024)
The online learning landscape in the Elementary Teacher Education (PGSD) program at Universitas Terbuka Makassar poses significant challenges for tutors, requiring them to adapt to new pedagogical approaches and technologies. This study investigates the competence of tutors in facilitating synchronous online-learning tutoring (Tuweb UT) and asynchronous Learning System Management (LMS) through Silayar UT, which integrates an independent learning program into online platforms. The study examines the tutors' social, strategic, and ethical competence in managing online classes, with a focus on their preparation, planning, and interaction with students. The study uses an ex post facto design with descriptive statistics, analyzing data from 185 tutors in 340 online classes within the undergraduate PGSD program during the 2022 registration term. The findings highlight the tutors' ability to prepare and plan for online tutoring, deploy the tutoring unit (SAT) as a learning service scheme, and incorporate relevant competencies and module characteristics into their tutoring mode. The study also shows that tutoring assignments are given in accordance with competence and that active engagement in Webinar UT and LMS (Silayar UT) is high, with attendance averaging 93.03%. The results indicate that tutors are competent in preparing and planning for online tutoring, incorporating online platforms into their experiences, and fostering active interaction with students, which in turn supports the completion of students' academic trajectories. The study's implications for online learning practices are significant, highlighting the importance of tutor competence in navigating the challenges of online education. Recommendations for further research include exploring the impact of tutor competence on student outcomes and investigating the role of technology in enhancing tutor-student interaction.